24.5k views
2 votes
Rewrite the rational expression as an equivalent rational expression whose denominator is the given polynomial

Rewrite the rational expression as an equivalent rational expression whose denominator-example-1

1 Answer

4 votes

Step 1

Given;


\begin{gathered} (-5y-3)/(30x^2+20)=(z)/(60x^2+40) \\ \text{where;} \\ z\text{ is the missing part of the equivalent rational }expression \end{gathered}

Required; To find the missing part of the equivalent rational expression.

Step 2

Cross multiply


\begin{gathered} (-5y-3)/(30x^2+20)=(z)/(60x^2+40) \\ z(30x^2+20)=(-5y-3)(60x^2+40) \\ \end{gathered}

Factorize 60x²+40


z(30x^2+20)=(-5y-3)(2(30x^2+20))

Divide all through by 30x²+20


\begin{gathered} (z(30x^2+20))/((30x^2+20))=((-5y-3)(2(30x^2+20)))/((30x^2+20)) \\ z=2(-5y-3) \\ z=-10y-6 \end{gathered}

Hence;


\begin{gathered} (-5y-3)/(30x^2+20)=(-10y-6)/(60x^2+40) \\ \text{Therefore, the missing part of the equivalent rational expression is;} \\ -10y-6 \end{gathered}

User Jan Hernandez
by
5.1k points